Kierkegaard, Jødedommen og Jøderne - Kirmmse, Bruce H. (Kirkehistoriske Samlinger, 1992)
Kierkegaard, Judaism, and the Jews Søren Kierkegaard mentions Jews and Judaism very frequently in his writings,1 and he often uses harsh and offensive language with respect to them, e.g.: “Goethe notes ... that the Jews’ murder of the Egyptians was the reverse of the Sicilian Vespers. There the host murdered the guests; in this case the guests murdered their hosts. But this is surely the Jews’ relationship to the whole of Europe in our times.”2 Kierkegaard’s interest in Jews should be viewed against the background of the general European and Danish anti-semitism of the period. In 1813 Denmark a underwent a serious debate on the extent to which a Jewish presence was helpful or harmful to the society and on whether there ought to be any Jews in Denmark at all, and in 1819 there were anti-semitic riots in the streets of Copenhagen which lasted for quite a while. But despite this background of anti-semitism, Kierkegaard’s language is notably sharper than that expressed by most educated people of his generation. Early on, Kierkegaard was fascinated with (and to some extent identified himself with) the character of the Wandering Jew, who was for Kierkegaard a romantic symbol of despair and of unforgivable sin, an outsider, an eternal wanderer with radical sin-consciousness. In his attitudes toward the actual Jews of his times, Kierkegaard tended to associate them with the aspects of modernity which made him uncomfortable: e.g., the triumph of the market economy, political struggles toward liberal representative government, and the development of the press and its role in shaping public opinion. Not surprisingly, Kierkegaard’s negative rhetoric in connection with these issues intensified after his collision with The Corsair and its editor Meir Aron Goldschmidt in 1846. Kierkegaard at first viewed Judaism as part of a three-stage development of religiosity: paganism (which he associates with the aesthetic stage), Judaism (which he associates with the ethical stage), and Christianity (which he associates with the religious stage).3 Judaism thus occupied a central, transitional role, and Kierkegaard was not unsympathetic to it. Gradually, however, his view darkened to a pure dualism in which Judaism (either alone or as a part of a new compound concept Kierkegaard calls “Judaism and paganism”4) come to stand as the opposite and enemy of Christianity, and not simply as its precursor. According to Kierkegaard, Judaism favors “Nature,” that is, “immediate” worldly comfort, instead of the Christian concentration upon “Spirit” and the suffering which is a part of the individual’s collision with the world.5 Judaism is thus portrayed as the religion of sexual self-indulgence, while Christianity is virtuous chastity.6 In the political sphere Judaism is portrayed as the religion of collectivity, while Christianity is higher and focuses upon the individual.7 Most of what Kierkegaard attributes to Judaism, however, is actually a critique of tendencies he found objectionable in his own officially Christian society, in which tranquility had triumphed over the unrest of the soul. Thus Kierkegaard repeatedly maintains that established Christendom is “Judaism”: “As I have noted elsewhere, the little bit of religiosity one sees in Christendom (and it is little enough) is really Judaism.”8 Grundtvig in particular, with what Kierkegaard saw as his excessive emphasis upon specific ritual language and upon the congregation as a people historically chosen by God, etc., was easily portrayed as “Jewish.” And Grundtvig’s enemy Bishop Mynster is also labelled “Jewish” for what Kierkegaard saw as his role in maintaining too close and comfortable a relationship between religion and the holders of social power. Thus a good deal of Kierkegaard’s critique of the established Christianity of his times was couched in anti-Jewish language, a rhetoric which intensified over time, and this accounts for much of his anti-semitism, which was in general not directed against actual Jews but against putatively Christian elements in his society. Quite properly, Kierkegaard’s antisemitic language is and remains offensive. The entire question of the origins and implications of Kierkegaard’s anti-semitic language deserves further investigation, and in connection with this it would also be useful to investigate the other forms of anti-semitism - which have been termed “the anti-semitism of tolerance” - that dominated Golden Age Denmark and that have continued to exist into our time. Notes 1. The present investigation traces Kierkegaard’s views on Jews and Judaism primarily through his entries in his Papirer [Journals and Papers]. The same pattern is visible in his published works, however, as the present investigation demonstrates in an appendix. 2. Cf. also Steen Johansen, ed., Erindringer om Søren Kierkegaard [Recollections About Søren Kierkegaard], 2nd augmented edition (Copenhagen: C. A. Reitzels, 1980), where Fr. Hammerich gives an account of a conversation he had with Kierkegaard: “One afternoon, I remember, I was going for a walk in the woods with my father, and he met us and his brother out near Bellevue. The weather was lovely. The sun played with the leaves, and the shadows were doubly dark in contrast to the clear, green light which shone through the leaves. I said something about it. ‘Oh, yes, you know,’ he said, ‘it’s pretty enough, but you get bored with that sort of soulless beauty. Do you think that’s why I come here? No. I have to take a bath, and in Copenhagen, of course, it’s swarming all over with Jew-boys [Hanjøder, literally “He-Jews”]. so I took a coach and got my bath, and now I’m finished and driving right home again” [p. 54]. 3. Papirer, vol. Ill A 102 (n. d., 1841), and ibid., bd. X 5 A 39, p. 41 (n. d. 1852). 4. Ibid., vol. X 5 A 65, p. 71 (n.d., 1853, between Jan. 4 and Feb. 13). 5. E.g., ibid., vol. IX A 424 (n.d., 1848, Nov. 26 or after). 6. E.g., ibid., vol. XI 1 A 150 and 169 (n.d., 1854, between May 5 and June 28). 7. Ibid., vol. XI 1 A 421 (n.d., 1854, between Aug. 16 and Nov. 26). 8. Ibid., vol. X 3 A 276, p. 205 (n.d., 1850, between June 11 and Sept. 11). See also, e.g., ibid., vol. IX A 301 (n.d., 1848, between Aug. 21 and Nov. 26) and vol. X 5 B 107, p. 289 (n.d., 1849).